2006
DOI: 10.1111/j.1939-165x.2006.tb00160.x
|View full text |Cite
|
Sign up to set email alerts
|

Hematology and plasma chemistry reference intervals for cultured shortnose sturgeon (Acipenser brevirostrum)

Abstract: Reference values reported here will be useful for the early detection, identification, and monitoring of disease and sublethal conditions in cultured shortnose sturgeon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
104
10
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(144 citation statements)
references
References 34 publications
28
104
10
2
Order By: Relevance
“…Hybridization produces animals with better performance than their parent species, and Heteroclarias has been reported to have faster growth rate, efficient feed conversion rate, resistance to diseases and high tolerance to environmental variations. These explain the higher values recorded in this study when compared with those of Adeyemo et al (2014) and Gabriel et al (2004) Also, the haematological parameters fell within the reference ranges reported in a cultured shortnose sturgeon but with slightly lower HBC and far higher MCV, MCH and WBC count (Knowles 2006). The PCV and WBC also fell within the reference ranges (30-34 %, 19.8-28.1×10 3 /μl) reported by Tripathi et al (2004) in koi (Cyprinus carpio), but higher HBC and RBC (6.30-7.60 g/dl and 1.70-1.90×10 6 /μl) count.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Hybridization produces animals with better performance than their parent species, and Heteroclarias has been reported to have faster growth rate, efficient feed conversion rate, resistance to diseases and high tolerance to environmental variations. These explain the higher values recorded in this study when compared with those of Adeyemo et al (2014) and Gabriel et al (2004) Also, the haematological parameters fell within the reference ranges reported in a cultured shortnose sturgeon but with slightly lower HBC and far higher MCV, MCH and WBC count (Knowles 2006). The PCV and WBC also fell within the reference ranges (30-34 %, 19.8-28.1×10 3 /μl) reported by Tripathi et al (2004) in koi (Cyprinus carpio), but higher HBC and RBC (6.30-7.60 g/dl and 1.70-1.90×10 6 /μl) count.…”
Section: Discussionsupporting
confidence: 72%
“…AST lies within the range in both the low and high-density systems in tilapia (ALT, 5-124 and 9-120 IU/l; ALP, 16-38 and 15-39 IU/l; total proteins, 2.30-3.60 and 2.9-6.6 g/dl; albumin, 1.0-1.6 and 1.3-2.6 mg/dl; globulins, 1.30-2.10 and 1.6-4.2 g/dl; calcium, 10.50-19.00 and 13.60-69.40 g/dl; BGL, 39.00-96.00 and 30-69 mg/dl; cholesterol, 64.00-299.00 and 110-318 mg/dl for low and high-density systems, respectively) (Hrubec et al 2000). Also, there were lower AST, ALP, calcium and higher plasma glucose levels than the ranges reported for the cultured shortnose sturgeon, while the cholesterol level lies within the reported range (total proteins, 2.7-5.3 g/dl; albumin, 0.8-1.7 g/dl; globulin, 1.80-3.70 g/dl; calcium, 6.60-12.10 mg/dl; AST, 90.00-311.00 IU/l; ALP, 47.00-497.00 IU/l; plasma glucose, 37.00-74.00 mg/dl; and cholesterol, 42.00-133.00 mg/dl) (Knowles et al 2006).…”
Section: Discussionmentioning
confidence: 98%
“…The serum alkaline phosphates activity of the sampled C. gariepinus catfish ranged from 18.53 to 42.11 IU/L with a median value of 22.40 IU/L. These values although similar to the values reported for C. gariepinus by Myburgh et al (2008), they were significantly higher than the values reported by Knowles et al (2006) for cultured Short Nose Sturgeon (Acipenser brevinostrum) and by Peres et al in Senegalese sole (Solae senegalensis).…”
Section: Serum Alkaline Phosphatase Activitysupporting
confidence: 68%
“…Serum biochemical parameters can vary within and between species of fish (Hrubec et al, 2001;Knowles et al, 2006), These values have also been reported to be dependent on the physico-chemical parameters of the culture water, health status and nutrition of the cultured organism (Farrell, 1997). The objective of the determination of serum biochemical reference intervals in apparently healthy subjects is to establish a basis for comparisons of suspected organ or system dysfunctions before the institution and or monitoring of interventions in farm or clinical settings (Langdon and Jones, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation